It's Not That Important: Demoting Personal Information of Low Subjective Importance Using GrayArea - Bergman, Ofer; Tucker, Simon; Beyth-Marom, Ruth; Cutrell, Ed; Whittaker, Steve (Proceedings of CHI 2009, Human Factors in Computing Systems, 2009)
Users find it hard to delete unimportant personal information which often results in cluttered workspaces. We present a full design cycle for GrayArea, a novel interface that allows users to demote unimportant files by dragging them to a gray area at the bottom of their file folders. Demotion is an intermediate option between keeping and deleting. It combines the advantages of deletion (unimportant files don’t compete for attention) and keeping (files are retrieved in their folder context). We developed the GrayArea working prototype using thorough iterative design. We evaluated it by asking 96 participants to ‘clean’ two folders with, and without, GrayArea. Using GrayArea reduced folder clutter by 13%. Further, 81% of participants found it easier to demote than delete files, and most indicated they would use GrayArea if provided in their operating systems. The results provide strong evidence for the demotion principle suggested by the user-subjective approach.